TRAINING ON FISHERY PRODUCT HANDLING IN NURUL HUDA ISLAMIC BOARDING SCHOOL SURABAYA - Lailatul Lutfiyah; Dwitha Nirmala; Rr Juni Triastuti; Sri Subekti (Universitas Airlangga, 2023)
Islamic boarding schools are one of the traditional Islamic-based educational institutions that study Islamic religious sciences as their main study and apply them as daily charity. In terms of the curriculum, Islamic boarding schools no longer only provide religious education, but currently Islamic boarding schools provide additional subjects such as scouting, martial arts and entrepreneurship; both in the field of plantations, catering, sewing, cooperatives and others. Fishery product processing training is one of the methods to support economic independence in the form of entrepreneurship in Islamic boarding schools. Processing of fishery products is an activity that is carried out in stages, sequentially, cleanly and hygienically, and fulfills the quality requirements in order to convert raw fishery products into final products. The target of this community service activity is to form a fishery product processing business activity at the Nurul Huda Islamic Boarding School in Surabaya that is solid and able to compete in the market continuously so as to make the Islamic boarding school an independent institution and have a sustainable business. The method used is the method of approach that is carried out, among others, namely the Participatory method. The results that have been obtained from this activity are the increased knowledge of Islamic boarding school students on the importance of sanitation and handling of fishery products (processed products in the form of fish nuggets and dragon feet). The activity was attended by 40 students, with education levels, namely junior high and high school. As many as 90% of the participants in the Fishery Products Handling Technique training wanted further activities to increase their knowledge in the field of handling fishery products.